Hypertelorbitism Corrected by Facial Bipartition Improves Exotropia. Issue 5 (14th March 2022) - Chen, Kevin; Duvvuri, Priya; Gibstein, Alex; Nakfoor, Bruce; Fisher, Mark; Kawamoto, Henry; Bradley, James P.
Abstract : Background: The purpose of this study was to detail perioperative ophthalmologic evaluations to characterize functional ocular outcomes after facial bipartition surgery. Methods: Patients with hypertelorbitism who underwent facial bipartition surgery were studied specifically for eye motility disorders by separating patients into rare craniofacial clefts (midline and paramedian) ( n = 34) and craniofacial dysostosis (Apert, Crouzon, and Pfeiffer) ( n = 74). Preoperative and postoperative (12 months) ophthalmologic examinations (with depth perception tests), computed tomography scans, and magnetic resonance imaging scans were analyzed. Results: Among craniofacial cleft patients, mean interdacryon distance was reduced from 39 ± 4 mm to 17 ± 2 mm, with strabismus improved from 88 percent (exotropia 82 percent) preoperatively to only 29 percent postoperatively. Depth perception improved to a lesser degree, with abnormal tests at a rate of 79 percent preoperatively to 56 percent postoperatively. Wider hypertelorbitism had a higher degree of strabismus. Among craniofacial dysostotic patients, mean interdacryon distance was reduced from 37 ± 3 mm to 17 ± 2 mm, and strabismus improved from 55 percent to only 14 percent. Depth perception improved to a lesser degree, with 68 percent abnormal tests preoperatively and 46 percent postoperatively. Apert patients had more V-pattern strabismus and exotropia (79 percent) than did other craniofacial dysostosis patients (42 percent). Conclusions: The authors' data indicate that facial bipartition for hypertelorbitism—known to improve periorbital aesthetics—also improves eye motility disturbances. Thus, vision problems related to exotropia should be considered a functional indication for facial bipartition surgery in patients with hypertelorbitism. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.